Fabrication and Characterizations of KCa2Fe4As4F2 Superconducting HIP Wires. (July 2020) - Pyon, S; Miyawaki, D; Tamegai, T; Kajitani, H; Koizumi, N; Awaji, S; Kito, H; Ishida, S; Yoshida, Y
Abstract: We report the fabrication and characterizations of KCa2 Fe4 As4 F2 round wires for the first time. Polycrystalline KCa2 Fe4 As4 F2 powder was prepared by solid-state reaction. Superconducting wires were fabricated by powder-in-tube (PIT) method followed by hot-isostatic-press (HIP) technique. The self-field J c of the KCa2 Fe4 As4 F2 HIP wires fabricated at 700 and 740°C at a high pressure of 9 MPa for 0.5 h, reached 10 kAcm −2 . Although high-pressure sintering at high temperatures enhanced the J c and density of the core of the wires, X-ray diffraction and scanning electron microscopy–energy-dispersive X-ray spectroscopy analyses indicated that impurity phases were present both in the polycrystalline powder and in the core of the wire.